Preposition Of Place In Minangkabau Language - Mac Aditiawarman (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Every preposition has its own meaning. Preposition. can provide a more detailed description of the sentences they occupy. This study used distributional method. The technique that apply in this reasearch are deletion (deletion), substitution, insertion, and removal of elements (permutation). From the results of this study found that, Minangkabau Prepeposition can be divided into 16 groups of meaning. The meaning of place can be divided into 3 parts, namely: (a) Locative static, (b) Locative purposes, and (c) Place of Origin (locative origin)